2020
DOI: 10.1109/tbdata.2018.2884505
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Unified Framework for Predicting Citation Dynamics

Abstract: With the rising interest in predicting the scientific output, various efforts have been made to predict a scientist's h-index or the citation trajectory of a publication. In this work, we employ a dynamic categorization for scientists to ensure at each stage of their careers a comparison amongst their peers and combine this grouping with predictive models to estimate a scientist's future impact, as expressed by citation counts. Moreover, we investigate a wide range of factors identifying their importance in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For the prediction task, they automatically generated 44 features for each scholar, such as publication and citation scores, h-index , and changes in citations, h-index , and mean number of citations per publication over the last two years, and used them in several regression models. Gogoglou and Manolopoulos [ 12 ] created clusters of academic peers according to their citation scores and predicted the future impact of the scholars that belong to each group based on several features such as: the publication and citation rates, co-authorship, citers and cited authors, differences in citations and h-index for every ten-year sub-period. They found that the position of the scholar within the social network of citers and cited authors is crucial for future impact.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…For the prediction task, they automatically generated 44 features for each scholar, such as publication and citation scores, h-index , and changes in citations, h-index , and mean number of citations per publication over the last two years, and used them in several regression models. Gogoglou and Manolopoulos [ 12 ] created clusters of academic peers according to their citation scores and predicted the future impact of the scholars that belong to each group based on several features such as: the publication and citation rates, co-authorship, citers and cited authors, differences in citations and h-index for every ten-year sub-period. They found that the position of the scholar within the social network of citers and cited authors is crucial for future impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies that compared scholarly productivity across disciplines found that the publication rates of natural scientists exceed those of social scientists and humanists [ 8 , [52] , [53] , [54] , [55] , [56] ]. According to Gogoglou and Manolopoulos [ 12 ] and Sarigöl et al [ 57 ], social links and networking of scholars may have effect on their future impact. In this study, our goal was to develop measures of scholarly impact that are not susceptible to biases toward certain fields, seniority levels or source citation index.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations